Strategy and skills in learning a foreign language - McDonough, Steven H (Edward Arnold, 1995)
This book examines the processes in involved in acquiring language skills, both mental and social, and the notion of what makes a skilled language learner. Throughout the discussion this book presents the growing body of knowledge from qualitative and descriptive ressearrch on second language development and draws implications for the development of teaching and learning strategies